2010
DOI: 10.1007/s12369-010-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Interactions with Physically Present Robots over Video-Displayed Agents

Abstract: This paper explores how a robot's physical presence affects human judgments of the robot as a social partner. For this experiment, participants collaborated on simple book-moving tasks with a humanoid robot that was either physically present or displayed via a live video feed. Multiple tasks individually examined the following aspects of social interaction: greetings, cooperation, trust, and personal space. Participants readily greeted and cooperated with the robot whether present physically or in live video d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(184 citation statements)
references
References 21 publications
7
175
1
1
Order By: Relevance
“…Previous studies have shown differences in both attitude and learning gains in a similar comparison [2,16]. However, in our study the two conditions were much more similar: the "virtual agent" had the same emotional sounds of excitement and frustration; the sound was emitted in both conditions from the speakers, for increased volume; there was no virtual character on the tablet.…”
Section: Curious Tablet Vs Curious Robotsupporting
confidence: 48%
See 2 more Smart Citations
“…Previous studies have shown differences in both attitude and learning gains in a similar comparison [2,16]. However, in our study the two conditions were much more similar: the "virtual agent" had the same emotional sounds of excitement and frustration; the sound was emitted in both conditions from the speakers, for increased volume; there was no virtual character on the tablet.…”
Section: Curious Tablet Vs Curious Robotsupporting
confidence: 48%
“…the same Story-maker app is used in exactly the same manner across conditions, we hypothesize that the children will learn new words, but not differently with respect to the curious and non-curious conditions. Nevertheless, we hypothesize that the robot conditions will have larger effects than the curious tablet condition, due to the physical embodiment of the robot [2].…”
Section: Hypothesismentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, Morita et al (2007) showed that the eye gaze of a remote person was more recognizable when reproduced by a robot than by a live video. Bainbridge et al (2011) explored how a robot's physical presence affects human judgments of the robot as a social partner. They found that participants were more likely to fulfill a trustrelated task when the robot was physically present, than when it was shown on live video.…”
Section: Robotmentioning
confidence: 99%
“…Recently, robot-mediated interaction has emerged as a viable option. These systems seek to increase the richness of the interaction and to improve communication channels by bringing them closer to face-to-face interaction (Bainbridge et al, 2011). The main distinctive feature of these systems is the physical presence of the robot.…”
Section: Introductionmentioning
confidence: 99%